Teaching and learning in multilingual contexts sociolinguistic and educational perspectives - Otwinowska, Agnieszka; De Angelis, Gessica 1965- (Bilingual education & bilingualism, 2014)
It is clearly illogical to search for one good, universal solution for multilingual education when educational contexts differ so widely due to demographic and social factors. The situation is further complicated by the motivations of learners and teachers, and by attitudes towards multilingualism and ‘otherness’. The studies in this volume seek to investigate not only whether certain solutions and practices are ‘good’, but also when and for whom they make sense. The book covers a wide range of Western multilingual contexts, and uncovers common themes and practices, shared aims and preoccupations, and often similar solutions, within seemingly diverse contexts. In addition to chapters based on empirical data, this book offers theoretical contributions in the shape of a discussion of the appropriateness of L1-Ln terminology when discussing complex multilingual realities, and looks at how the age factor works in classroom settings